Web Accessibility Status of Open Access Journals in Africa: A 2024 Snapshot - Pastor Nso-Mangue; Sergio Luján-Mora (Journal of Computer Sciences Institute)
Open access journals (OAJs) allow access to scientific articles free of charge worldwide. Therefore, OAJs plays an important role in disseminating scientific knowledge to the world. The access to OAJs is primarily via the Web, which still present barriers to persons with disabilities. Currently, 16% of the world's population lives with some form of disability and cannot enjoy equal access to the Web. Access to the Web is a human right under the Convention on the Rights of Persons with Disabilities (CRPD) and a key aspect of achieving the Sustainable Development Goals. In Africa, approximately 80 million people with disabilities face barriers to equal access to the Web. Despite the potential benefits of the adoption of OAJs in developing countries, there are not a lot of studies on their accessibility by persons with disabilities. The purpose of this study is to evaluate the Web accessibility of OAJs in Africa against the Web Content Accessibility Guidelines (WCAG). A selection of OAJs, from the Directory of Open Access Journals (DOAJ), is evaluated against WCAG 2.1 using three automated web accessibility evaluation tools (AWAETs): Mauve++, Lighthouse and WAVE. The results show that African OAJ websites are not fully compliant to WCAG 2.1. Although in average, the performance is good, further improvements are needed to ensure equal access to all, by reducing errors and increasing the implementation of Accessible Rich Internet Applications (ARIA).